An analysis of medication errors in patients admitted to surgery rooms and post-anesthetic recovery at a high-complexity hospital in Bogota, Colombia - Ángel Humberto Villanueva; José Julián López Gutiérrez (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Medication errors represent one of the main causes of incidents and adverse events during the perioperative period. Therefore, this study analyzes errors before, during, and after the administration of general anesthesia for abdominal surgery at a high-complexity hospital in Bogota, Colombia. A descriptive cross-sectional study was conducted with 390 patients between January and September 2019. Of the 3,677 medication administrations, some type of error was made in 60% of cases, mostly in emergency surgeries. The pharmacological group with the most errors was general anesthetics, with 32%. All identified errors constituted situations with harm potential, indicating the need to promote the standardization of activities involving the use of medications and a culture of healthcare safety in order to avoid adverse events.